1976
DOI: 10.1007/bf00162453
|View full text |Cite
|
Sign up to set email alerts
|

The fine structure of prominences

Abstract: The fine structure of nonspot prominences are studied from Ha filtergrams. The size of the smaIlest prominence structures increases with height above the chromosphere. Some prominences contain structures close to 89 arc second, which is the spatial resolution in the present data. The effective thickness of many nonspot prominences ranges between 4 • 107 cm and 1.5 x 108 cm. An apparent downward directed motion is observed in the majority of the prominences. No preferred direction of the motion is seen in regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(53 citation statements)
references
References 19 publications
4
49
0
Order By: Relevance
“…While some theoretical models consider prominences as an infinite slab of plasma having a small thickness, many observations of quiescent prominences show very fine structures in the body of the filament, suggesting that they are composed of small-scale threads. The existence of this internal structure in prominences was already suggested by Menzel & Evans (1953) and was clarified with the improvement of observational capabilities (Engvold 1976;Engvold et al 1987). Although vertical filamentary structures can be seen in limb prominences (Dunn 1960), there is also evidence for the existence of horizontal fine structures within prominences (Schmieder & Mein 1989;Schmieder et al 1991).…”
Section: Introductionmentioning
confidence: 67%
“…While some theoretical models consider prominences as an infinite slab of plasma having a small thickness, many observations of quiescent prominences show very fine structures in the body of the filament, suggesting that they are composed of small-scale threads. The existence of this internal structure in prominences was already suggested by Menzel & Evans (1953) and was clarified with the improvement of observational capabilities (Engvold 1976;Engvold et al 1987). Although vertical filamentary structures can be seen in limb prominences (Dunn 1960), there is also evidence for the existence of horizontal fine structures within prominences (Schmieder & Mein 1989;Schmieder et al 1991).…”
Section: Introductionmentioning
confidence: 67%
“…5. Many authors have observed the presence of threads in filaments and prominences before (e.g., Menzel & Wolbach 1960;Engvold 1976;Lin et al 2005Lin et al , 2008Okamoto et al 2007). It is generally believed that dark thin features in the chromosphere near ARs trace magnetic field lines.…”
Section: Tip-ii Observationsmentioning
confidence: 99%
“…The overall structure of quiescent prominences changes little with time, preserving their shape during days and even weeks. Locally, they consist of fine and vertically oriented plasma structures, so-called threads, that evolve continually (e.g., Engvold 1976;Zirker et al 1994). Recent ob-A movie is available in electronic form at http://www.aanda.org 1 There are many papers about solar prominences, but we recommend that the reader first go through the historical work of Einar Tandberg-Hanssen (e.g., Tandberg-Hanssen 1998, 2011 servations taken with the Hinode satellite have revolutionized our knowledge of the fine-scale structuring and dynamics of quiescent prominences; for instance, plasma oscillations, supersonic downflows, or plasma instabilities like the Rayleigh-Taylor instability in prominence bubbles (Berger et al 2008(Berger et al , 2010Chae et al 2008;Okamoto et al 2007).…”
Section: Introductionmentioning
confidence: 99%